الرجال الذين أخرج لهم الإمام مسلم وضعفهم الإمام أبو العرب القيرواني - عامر, علي; الزاوي, عبد الوهاب (University of eloued جامعة الوادي, 2021)
تطرّقت هذه المذكرة إلى دراسة مجموعة من الرواة الذين اخرج لهم الإمام مسلم في صحيحه سواء في الأصول أو في المتابعات، وضعفهم الإمام أبو العرب القيرواني، وتمت فيها الدراسة بداية بتعريف بالإمامين مسلم وأبي العرب، ثم تناولت بعض القضايا الخاصة بالجرح والتعدي ككيفية جمع أقوال الأئمة المختلفة، ثم ركزت على الدراسة التطبيقية من خلال إحصاء كامل الرواة وقد بلغ عددهم سبعة عشر راوياً، فكان عدد الذين أخرج لهم في الأصول سبعة والباقي في المتابعات، فأثبتت فيهم قول أبي العرب أولاً، ثم أردفت أقوال النقاد الموافقين له والمخالفين، وتتبّعتْ بعد ذلك خلاصة الحكم على هذا الراوي من خلال الجمع والمقارنة بين أقوال النقاد، ثم تطرقتْ إلى كيفية إخراج الإمام مسلم لهؤلاء الرواة، محاولة الجمع بين خلاصة الحكم على الرواة من قبل النقاد ومنهجية إخراج الإمام مسلم في صحيحه، فخلُصتْ إلى أن ستة منهم تضعيفهم كان يسيرً فيحتملُ منهم في المتابعات والشواهد، وسبعةُ منهم الراجح فيهم أنهم ثقات فروايتهم صحيحة والأربعة الباقية كان تضعيفهم بسبب بدعتهم لكن الإمام مسلم أخرج ما صح عنهم، وأوصتْ هذه الدارسة بمزيد من دراسة مناهج المحدثين المغاربة.This note dealt with the study of a group of narrators whom Imam Muslim brought out in his Sahih, whether in the origins or in the follow-ups, and they weaknessed by Imam Abu Al-Arab Al-Qayrawani, and the study was carried out in the beginning with a biography of the two Imams Muslim and Abi Al-Arab, and then dealt with some issues related to injury and transgression as how to collect the sayings of the different imams Then I focused on the applied study by counting the entire narrators, and their number reached seventeen, so the number of those he brought out for them in the origins was seven and the rest in the follow-ups, so I proved in them the sayings of Abi Al-Arab first, then the sayings of critics who agreed with him and those who disagreed were followed, and then followed the summary of the judgment On this narrator by collecting and comparing the sayings of critics, then touched on how Imam Muslim extracted these narrators, trying to combine the summary judgment on the narrators by critics and the methodology of Imam Muslim’s output in his Sahih, so she concluded that six of them were weak, so it is possible from them in the follow-ups And the evidence, and seven of them are most likely to be trustworthy, so their narrations are authentic, and the remaining four were weak because of their heresy, but Imam Muslim brought out what is authentic about them, and this study recommended further study of the curricula of the Maghreb hadith schol
علوم حديث
Keywords: أبو العرب القيرواني، الرواة، مسلم ، الجرح والتعديل .; Abu al-Arab al-Qayrawani, the narrators, Muslim, al-Jarh wa al-Ta’deel.